Principles of health promotion and disease prevention in islamic medical philosophy - Shogar, Ibrahim (2016)
The purpose of this paper is to advocate for an alternative philosophy of medicine that capable of addressing all aspects of medical research, the ethical, epistemological and metaphysical problems. The basic presupposition of the paper is that the Islamic principles on promoting health and preventing disease could play an important role in developing such a holistic approach. Utilizing the traditional method of analysis, the paper has investigated the three major frameworks of explanation that dominated the history of medical philosophy: (a) the humoral model, which based on balance of the humors; (b) modernity model, which based on causal explanation; and (c) the post-modern model that emphasizes the probabilistic method of interpretation. The paper investigated the three forms of explanation that based on the above domains, (i) the normative, (ii) the descriptive, and (iii) integrated; and traced their impact on good medical practices. The paper especially explored principles of Islamic medical philosophy and its role in promoting the holistic medical philosophy. Along the way, the paper has discussed the ideal relationship between physician and patient according to Islamic perspective.